Hyperemesis gravidarum and birth weight. Maternal Perinatal National Institute. Year 2008 - admin, admin (2018)
Objectives. To determine the relation between hyperemesis gravidarum and the newborn weight at Maternal Perinatal National Institute during 2008. Materials and methods. A correlational retrospective study was carried out in 120 pregnant women with hyperemesis gravidarum who were seen from January to december in 2008 at this institute. A documentary observation method was utilized in the clinical records, and some investigation about the general characteristics involving mothers and newborns was also made. The datum were analyzed through significant descriptive and inferential statistics with hypothesis testing at a level of statistical significance p<0,05. Results. The hyperemesis gravidarum incidence is 0,69. The average age of the pregnant women that were evaluated is 27,3 ± 6,2; an average height of 1,54 ± 0,06; an average pregestational weight of 58,4 ± 7,9; an average body mass index of 24,6 ± 3,2; and an average hemoglobin level of 12,7 ± 1,2. From the evaluation of the results, it is clear that the average weights of the newborns in the severe and moderate hyperemesis gravidarum are similar. There is statistical evidence at a 95% confidence level to affirm that there is not any relation between these variables: the newborn weight and the severity degree of hyperemesis gravidarum p=0,83. Conclusion.The effects of hyperemesis gravidarum do not have any relation with the newborn weight.